PENGEMBANGAN BAHAN AJAR MOBILE LEARNING PADA MATERI PELUANG UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK - Septiawati, Farida; Zahroh, Umy; Sutopo, Sutopo (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The background of this research is the lack of flexibility in the teaching materials used in learning. The use of less interesting teaching materials reduces students' interest in learning and their mathematical communication skills tend to be low. Technological advances require developers to develop interesting and flexible teaching materials. This research aims to: (1) Describe the process of developing mobile learning teaching materials to improve vocational school students' mathematical communication skills, (2) Find out the feasibility of mobile learning teaching materials to improve vocational school students' mathematical communication skills, (3) Find out the effectiveness of mobile learning teaching materials for improve vocational school students' mathematical communication skills. This research uses the Borg and Gall development model. Validation tests were carried out by 2 material experts and 2 media experts. Product trials were carried out in 2 stages, namely limited group trials and field implementation trials. This development obtained the results of the validity of teaching materials by media experts with a percentage of 85% in the valid category. The results of the validity of teaching materials by material experts with a percentage of 89% are in the valid category. The results of the practicality of teaching materials were obtained from the analysis of user activity observations, the percentage of students asking questions was 20% with the criteria that they could be used without revision. Meanwhile, the results of the teacher response questionnaire obtained a percentage of 97% with very practical criteria for use in learning. The student response questionnaire obtained a percentage of 95%, the criteria were very effectively used.